Increased damage to type II collagen in osteoarthritic articular cartilage detected by a new immunoassay. - Hollander, A P (1994)
A new immunoassay was developed to detect denaturation of type II collagen in osteoarthritis (OA). A peptide, alpha 1 (II)-CB11B, located in the CB11 peptide of type II collagen, was synthesized and used to produce a monoclonal antibody (COL2-3/4m) of the IgG1 (kappa) isotype. This reacts with a defined epitope in denatured but not native type II collagen and the alpha 3 chain of type XI collagen. The latter is present in very small amounts (about 1% wt/wt) in cartilage relative to the alpha 1 (II) chain. By using an enzyme-linked immunosorbent assay, type II collagen denaturation and total type II collagen content were determined. The epitope recognized by the antibody was resistant to cleavage by alpha-chymotrypsin and proteinase K which were used to extract alpha 1 (II)-CB11B from the denatured (alpha-chymotrypsin soluble) and residual native (proteinase K soluble) collagen alpha-chains, respectively, present in human femoral articular cartilage. Type II collagen content was significantly reduced from a mean (range) of 14% (9.2-20.8%) of wet weight in 8 normal cartilages to 10.3% (7.4-15.0%) in 16 OA cartilages. This decrease, which may result in part from an increased hydration, was accompanied by an increase in the percent denaturation of type II collagen in OA to 6.0% of total type II collagen compared with 1.1% in normal tissue. The percent denaturation was ordinarily greater in the more superficial zone than in the deep zone of OA cartilage.